Botanical origin and chemical composition of bee pollens collected from Apis cerana hives domesticated in the Pauri Garhwal, Western Himalaya, India - Bagri, Ajendra singh; Tiwari, Prabhawati; Gloch, Eza (Ecological Questions, 2023)
The present investigation aims to determine the botanical origin and chemical composition of bee pollen samples (n =22) harvested from Apis cerana hives domesticated in Pauri Garhwal (Uttarakhand, India). The majority (95%) of the samples were unifloral in their botanical origin. All the identified pollens belonged to eighteen plant families, among which Rutaceae, Asteraceae and Brassicaceae were found dominant. The chemical parameters soluble sugars, starch, crude protein, amino acids and phenolic contents were analyzed calorimetrically and were found in the range from 0.2 to 26.09 mg/g, 0.22 to 11.04 mg/g, 13.40 to 191.41 mg/g, 2.01 to 6.48 mg/g, and 5.10 to 35.50 mg GAE/g, respectively. Statistically significant differences (p<0.05) were observed between the chemical contents of the analyzed samples and a moderate correlation (r= 0.40; n=22) was observed between total soluble sugars and crude protein. Bee pollens as a good source of nutrition, medicine and dietary supplement for both humans and bees, demonstrate the important need to define bee pollen from different regions of India in order to develop bee pollen quality standards.